Innovative cost management technologies in the context of production digitalization - Chernyshenko, O. I. (WSEH, 2025)
The digitalization of production processes has transformed traditional approaches to cost management, introducing innovative technologies that enhance efficiency, transparency, and strategic decision-making. Modern tools such as big data analytics, cloud-based accounting systems, and artificial intelligence enable real-time monitoring of expenses, predictive modeling, and optimization of resource allocation. These technologies support the integration of cost management into digital production platforms, ensuring adaptability to dynamic market conditions and compliance with regulatory standards. By leveraging digital innovations, enterprises can reduce operational risks, improve competitiveness, and achieve sustainable economic growth.
Keywords: cost management; production digitalization; big data analytics; artificial intelligence; cloud technologies; resource optimization; competitiveness; sustainability